2019
DOI: 10.1017/s0263574719001632
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Reinforcement Learning in Mobile Robots Through Spiking Architecture of Thalamo-Cortico-Thalamic Circuitry of Mammalian Brain

Abstract: Summary In this paper, the behavioral learning of robots through spiking neural networks is studied in which the architecture of the network is based on the thalamo-cortico-thalamic circuitry of the mammalian brain. According to a variety of neurons, the Izhikevich model of single neuron is used for the representation of neuronal behaviors. One thousand and ninety spiking neurons are considered in the network. The spiking model of the proposed architecture is derived and prepared for the learning problem of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…9, which clearly reflects the comparison of the detection accuracy of the four VD algorithms network, to better reflect the improvement of the detection accuracy of the VD algorithms, also the more common VD algorithms and YOLOv5 combined with the CA mechanism of the network for comparison. It can be clearly found that the overall trend of the four VD algorithms is similar, and the detection accuracy in bus classification is much higher than the other classifications, at more than 90%, and the detection accuracy of the four algorithms for car classification is lower all approximating 83%, which may be due to the relatively fixed bus shape with obvious signs [19][20][21]. The YOLOv5 performance combined with CA mechanism for VD algorithm is significantly greater than the others, with detection accuracy exceeding other algorithms by about 0.8 percentage points.…”
Section: B Model Vehicle Inspection Quality Analysismentioning
confidence: 94%
“…9, which clearly reflects the comparison of the detection accuracy of the four VD algorithms network, to better reflect the improvement of the detection accuracy of the VD algorithms, also the more common VD algorithms and YOLOv5 combined with the CA mechanism of the network for comparison. It can be clearly found that the overall trend of the four VD algorithms is similar, and the detection accuracy in bus classification is much higher than the other classifications, at more than 90%, and the detection accuracy of the four algorithms for car classification is lower all approximating 83%, which may be due to the relatively fixed bus shape with obvious signs [19][20][21]. The YOLOv5 performance combined with CA mechanism for VD algorithm is significantly greater than the others, with detection accuracy exceeding other algorithms by about 0.8 percentage points.…”
Section: B Model Vehicle Inspection Quality Analysismentioning
confidence: 94%
“…Several studies have investigated the use of SNNs in designing robot control systems. For example, Azimirad and Sani [14] analyzed using SNNs inspired by the brain's circuitry for robot behavioral learning. They found that teaching the spiking architecture of these circuits can lead to successful target attraction.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcement learning (RL) is achieved by trial-and-error without prior labeled datasets and has been widely used in many fields including games, robots, and autonomous vehicles [22][23][24]. Some research uses RL algorithms to learn instrument-manipulation skills based on vectorized lowdimensional representations of VIS scenarios [21,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%